Can Syndecan-1 Be Used As A Biomarker In Alzheimer’s Disease? - Tuna Doğrul, Rana; Cavusoglu, Cagatay; Sengul Aycicek, Gozde; Ozsurekci, Cemile; Caliskan, Hatice; Doğan Varan, Hacer; Dikmen, Zeliha Gunnur; Halil, Meltem Gülhan; Cankurtaran, Mustafa; Dogu, Burcu Balam (Acta Medica, 2022)
Background: Syndecan-1 (SDC-1) is a member of the syndecan family, which includes heparan sulfate proteoglycans. SDC-1 is important for cell-cell and cell-matrix interactions. The aim of this study is to examine the relationship between serum SDC-1 levels and mild cognitive impairment (MCI) and Alzheimer’s disease (AD). Methods: Eighty-two patients aged 65 years and over were included in the study. The Mini-Mental State Examination (MMSE) was used to evaluate the cognitive functions of the patients. Comprehensive geriatric assessment components were administered to the patients. Serum SDC-1 levels were measured with an enzyme-linked immunosorbent assay kit. Results: When patients were grouped as control, MCI and AD, significant decreases were observed in Katz daily living activity (p<0.001), Lawton instrumental daily living activity (p=0.001), Mini-nutritional assessment (p=0.001), MMSE (p=0.001) scores. SDC-1 level was 154.88±22.85 in the control group, 157.95±19.45 in the MCI group, and 159.54±14.04 ng/mL in the AD group, and no significant correlation was observed (p=0.677). When correlation analyzes were performed with SDC-1, a negative correlation was found with the Yesavage geriatric depression scale score (Spearman rho: -0.223 p=0.044). Conclusion: No correlation was found between SDC-1 level and AD, and it showed a negative correlation with depression. Clarifying the pathogenetic processes more clearly will guide the development of new treatment strategies.